2020
DOI: 10.1007/s10584-020-02836-w
|View full text |Cite
|
Sign up to set email alerts
|

An equity analysis of clean vehicle rebate programs in California

Abstract: Rebates incentivize clean vehicle adoption but may raise equity concerns because upfront capital is required for vehicle acquisition, limiting access for low-income households. Since poorer communities typically experience worse air quality than their wealthier counterparts, rebates also may not incentivize clean vehicle acquisitions in more polluted areas where air quality benefits would be greater. We analyzed whether equity-promoting policy design elements changed the associations between rebate allocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…However, high-income buyers would purchase PEVs regardless of incentive availability [11], while lower income buyers' purchase decisions are more dependent on incentives [30,31]. Despite this, recipients of incentives are predominantly high-income buyers in predominantly white communities [32]. DeShazo et al [33] simulated the impact of income and purchase price caps on the CARB-funded California Clean Vehicle Rebate Project (CVRP).…”
Section: Electric Vehicle Buyersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high-income buyers would purchase PEVs regardless of incentive availability [11], while lower income buyers' purchase decisions are more dependent on incentives [30,31]. Despite this, recipients of incentives are predominantly high-income buyers in predominantly white communities [32]. DeShazo et al [33] simulated the impact of income and purchase price caps on the CARB-funded California Clean Vehicle Rebate Project (CVRP).…”
Section: Electric Vehicle Buyersmentioning
confidence: 99%
“…Research by Guo and Kontou [5] shows that income caps introduced in the CVRP did marginally increase the share of rebates being allocated to lower income households. The Clean Cars 4 All Program, with stricter income caps, more progressive rebate amounts, and greater availability to used car buyers increased rebate allocation in disadvantaged, lower income, lower education, and Hispanic communities [32,34].…”
Section: Electric Vehicle Buyersmentioning
confidence: 99%
“…Supporting these views, Rubin and St. Louis [42] and Ju et al [38] assessed California's Clean Vehicle Rebate Project (CVRP) with both studies showing similar results. They found that the CVRP program generated greater benefits to wealthier neighbourhoods, with higher levels of education and with fewer people of colour and Hispanics.…”
Section: Rebates and Equitymentioning
confidence: 91%
“…For instance, Hardman et al [35] and Snelling [37] note that to acquire these incentives, first, consumers need to purchase the vehicle, presenting a critical barrier for those with limited financial resources or those who lack access to credit. On the same vein, Ju et al [38] argue that for lowerincome consumers, rebate programs for EVs can become even less accessible if the refund amount does not increase according to income. Indeed, evidence indicates that wealthier consumers are not only more likely to adopt these vehicles [39] but also, that incentives are not reaching nor designed for the intended consumers due.…”
Section: Rebates and Equitymentioning
confidence: 99%
“…For example, one study found low income households in the metro Atlanta area were less likely to be eligible for ZE LDV federal tax credits due to factors such as tax bracket and family makeup (Liu et al, 2020). On a state level, researchers at UC Berkeley found California's Clean Vehicle Rebate Project (CVRP) has issued a larger number of ZE LDV rebates per capita to higher-income, whiter communities (Ju et al, 2020). Programs such as CVRP often use rebates, which are difficult for lower income households to take advantage of.…”
Section: Barriers To Ice Ldv Alternativesmentioning
confidence: 99%